Upaya Perpustakaan dalam Membangun Kolaborasi Riset Pustakawan di Universitas Sebelas Maret Surakarta - Siti Nurkamilah; Wahid Nashihuddin (Institut Agama Islam Negeri (IAIN) Curup, 2021)
One of the ways to increase librarian's scientific publications is through research collaboration. Research collaboration is an intellectual activity that emphasizes the need for collaboration, communication, and the division of tasks of the research team in a research project. Librarians can carry out research collaborations with academics to enhance their role as research collaborators for institutions. The UNS Library has provided research information and research consulting services called